Intrathymic differentiation of natural antibody-producing plasma cells in human neonates - Hector Cordero (Nature Portfolio, 2021)
The thymus is known as the organ of T lymphocyte development. Here authors show that terminal B cell differentiation also takes place in the thymus of human neonates, leading to antibody production against commensal and pathogenic bacteria.